(untitled) (Plant Tissue Culture and Biotechnology, 2014)
Solanum pseudocapsicum L. is an unexplored plant of Solanaceae having horticultural and medicinal importance. Earlier the in vitro morphogenic potential of this plant species has not been explored. Induction of direct organogenesis was obtained from internodes, leaf bases and root explants from in vitro grown seedlings and plants in MS supplemented with different concentrations and combinations of BAP (0.44 - 8.88 µM/l) and IAA (0.29 - 2.85 µM/l). Direct organogenesis was achieved in 90% of internodes, 65% of leaf bases and 75% of root explants. The optimum regeneration medium was MS supplemented with 4.44 µM/l BAP and 1.43 µM/l IAA. The regeneration rate observed six weeks after culture was approximately 20, 9 and 12 shoot buds/explants from internodes, leaf bases and root explants, respectively. cDNA RAPD analysis from organogenic stages was carried out and revealed distinct gene expression pattern. In vitro rooting in 100% shoots was achieved on MS within ten days of culture. Successfully hardened rooted plants (R0) on transfer to the field produced flowers, fruits and viable seeds (R1). Genetic characterization of R0 and R1 plants revealed stability and uniformity at the chromosomal and genomic DNA level. Plant Tissue Cult. & Biotech. 24(1): 65-76, 2014 (June) D. O. I. http://dx.doi.org/10.3329/ptcb.v24i1.19201